Effects of anesthetics on development of gynecological cancer - Cheng, Yingxiang; Wu, Yunzhi; Xu, Lingzhong (Frontiers in Cell and Developmental Biology, 2025)
Gynecological cancers remain a leading cause of cancer among female patients, and surgery continues to be the primary therapeutic approach. Anesthesia is an indispensable component of perioperative period. In recent years, the influence of anesthesia drugs on cancer has become one of the focuses of anesthesiologists. Anesthetic drugs may influence cancer metabolic reprogramming and modulate immune function through the hypothalamic-pituitary-adrenal (HPA) axis and the sympathetic nervous system (SNS). Emerging evidence suggests that the choice of anesthetic agents could affect the prognosis of gynecological cancers. This review explores the relationship between anesthetic drugs and gynecological cancers (cervical cancer, ovarian cancer, and endometrial cancer), elucidating their effects on cancer prognosis through cellular pathways, metabolic regulation, and immune mechanisms. The findings aim to guide clinical decision-making and evaluate optimal perioperative anesthetic management strategies for gynecological cancer patients.